2016
DOI: 10.1097/mat.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1-Positive Lymphocytes in Acute Cellular Cardiac Allograft Rejection: Contributor to Pathogenesis and a Therapeutic Target

Abstract: Cardiac allograft rejection remains a problem, despite advances with immunosuppressants. Understanding the mechanisms behind rejection is essential for developing targeted therapies. The goal of this investigation is to explore Sirtuin 1 (Sirt1) as a therapeutic target for cardiac allograft rejection. Thirteen endomyocardial biopsy specimens with acute cellular rejection (grade 2R or 3R) were selected. CD3, CD4, CD8, CD20, CD68, T-cell intracytoplasmic antigen (TIA-1), and Sirt1 expressions were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Most of the studies (9/16, 56.3%) dealt with graft rejection and quantification of parameters that aid in grading the severity of rejection or help elucidate potential pathogenetic mechanisms. Features quantified with DIA software included myocyte diameter,[45] fibrosis with Masson's trichrome stain,[4546] microvasculature density with CD31[46] or CD34,[47] patterns of inflammatory and immunological cells,[48] monocytes and macrophage profiles,[49] expression of Sirt1, CD8, and FoxP3 on lymphocytes in rejection specimens,[50] and chromatin remodeling expressed as mean gray level. [51] In some publications, digital images were converted in formats adequate for fractal analysis to quantify the inflammatory infiltrate and signs of myocyte damage; it was shown that this kind of DIA can discriminate among different grades of rejection.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies (9/16, 56.3%) dealt with graft rejection and quantification of parameters that aid in grading the severity of rejection or help elucidate potential pathogenetic mechanisms. Features quantified with DIA software included myocyte diameter,[45] fibrosis with Masson's trichrome stain,[4546] microvasculature density with CD31[46] or CD34,[47] patterns of inflammatory and immunological cells,[48] monocytes and macrophage profiles,[49] expression of Sirt1, CD8, and FoxP3 on lymphocytes in rejection specimens,[50] and chromatin remodeling expressed as mean gray level. [51] In some publications, digital images were converted in formats adequate for fractal analysis to quantify the inflammatory infiltrate and signs of myocyte damage; it was shown that this kind of DIA can discriminate among different grades of rejection.…”
Section: Methodsmentioning
confidence: 99%
“…While advances have been made in long-term survival following transplantation, current immunosuppressive therapies are known to promote infections and cancer. There is speculation that SIRT1 inhibitors may enhance the function of Treg cells to support immune suppression and allograft tolerance (84). Additionally, SIRT1 inhibitors may also confer prolonged allograft survival through the suppression of Th17 activity, as evidenced by decreased IL-17A (85); however, these results are in direct opposition to the SIRT1-activating and anti-tumor properties of metformin described above (44), and further studies are needed.…”
Section: Modulating Sirtuin Activity To Alter Immune Outcomes In Vivomentioning
confidence: 99%
“…In the process of acute cellular rejection, naive CD4 þ T helper (Th) cells under the influence of antigen and cytokine stimulation shift to Th1 and Th17 phenotypes with a concomitant decrease in T regulatory cells. 7 Lenalidomide, an analogue of thalidomide, is an immunomodulatory agent approved for clinical use in the treatment of some myelodysplastic syndromes and multiple myeloma. Its effects on the immune system are complex, as it demonstrates select anti-inflammatory properties by reducing release of pro-inflammatory cytokines tumor necrosis factor a, interleukin (IL) 1, IL-6, and IL-12 and stimulating an increase in IL-10, IL-2, and interferon (IFN) g involved with T-cell mediated immunity.…”
Section: Practice Issuesmentioning
confidence: 99%